A simple instrument for the assessment of student performance in problem-based learning tutorials. - Sim, Si Mui; Mohd Adnan, Nor Azila; Lian, Lay Hoong; Tan, Christina Phoay Lay; Tan, Nget Hong (Academy of Medicine, Singapore, 2006)
INTRODUCTION: A process-oriented instrument was developed for the summative assessment of student performance during problem-based learning (PBL) tutorials. This study evaluated (1) the acceptability of the instrument by tutors and (2) the consistency of assessment scores by different raters.